Mutation in the beta-myosin heavy chain (β-MHC) gene of adult Bangladeshi patients with hypertrophic cardiomyopathy (Bangabandhu Sheikh Mujib Medical University Journal, 2023)
Hypertrophic cardiomyopathy (HCM) is the most prevalent genetic cardiomyopathy characterized by sudden cardiac death. HCM is caused by the mutation in several genes that encode sarcomere proteins. Beta-Myosin Heavy Chain (β-MHC) gene is the one of the most mutated genes responsible for HCM. Studies on mutation spectrum of β-MHC gene are lacking in the Asian population including Bangladeshi patients. This study was intended to mutational analysis of β-MHC gene in Bangladeshi HCM patients. A cross-sectional study was conducted for mutation analysis of the β-MHC gene on 70 Bengali Bangladeshi HCM probands using nextgeneration sequencing at the Genetic Research Lab of Bangabandhu Sheikh Mujib Medical University. Structural and functional impact of the mutations were further analyzed by in-silico process. Thirty-nine nucleotide variants were found in both exonic (36%, n= 14) and intronic regions (64%, n=25) of β-MHC gene. We found 14 missense mutations, including the p.Glu965Lys, p.Arg941Pro, p.Lys940Met, p.Glu935Lys, and p.Met922Lys that are associated with inherited HCM. Most variants were heterozygous and one homozygous (p.Val919Leu) was found. The variant with most evidence of causing the disease was p.Glu935Lys. Among the missense variants, nine were not noted in ClinVar, dbSNP, GenomeAD databases. These unreported variants located between myosin head and tail domains might be novel mutations for Bangladeshi population. We found nine novel variants in the β-MHC gene. Findings of this research will help to developing a genetic database of HCM for early diagnosis and proper management of HCM patients in Bangladesh.